A simulation of increasing rice price toward the disparity of income distribution: An evidence from Indonesia. Issue 3 (March 2023) - Fitrawaty,; Hermawan, Wawan; Yusuf, Muhammad; Maipita, Indra
Abstract: Purpose: Considering the significance of rice as a staple food in Indonesia, this study aims to analyze the impact of various factors, i.e., domestic price production level, exchange rate, international rice price, and Gross Domestic Product (GDP) per capita, on domestic rice prices and the resultant disparity in income distribution and inequality in the country. Methods: A simulation analysis has been performed to assess the impact of the above-mentioned factors on rice prices and the resultant income disparity in Indonesia. For that, input data from 2006 to 2020 was used to depict the change in domestic rice prices from 2021 to 2026 due to independent variables changes. Findings: Results revealed that a regular increase in rice production decreases rice prices in the longer term. Besides, a rise in the exchange rate decreases rice prices, and a fall in the exchange rate results in higher rice prices. Results also showed the insignificant impact of international rice prices on domestic rice prices in Indonesia. In contrast, an increase in per capita income reflected an increase in rice prices. Moreover, the result of the study exemplifies that the expenditure for rice has a very low elasticity (0.0975) compared to the expenditure on non-rice food (0.4096). More than half of the total household expenditure (50.71%) is spent on food, while the rest (49.29%) is used for non-food. The increase in rice prices affects the rise of income amongst farmers and declines the income of non-farmers. Hence it affects the decline of disparity in households' income distribution. Originality/value: This study adds value to the existing literature with several implications for practitioners, policymakers, and government organizations to take necessary measures to stabilize rice prices and income distribution among the various income groups.